Research on the Technology of Cloud Media for the Video Conference System - Hai Sun; Minrui Shi; Ting Huang (Dianxin kexue)
It is a trend that cloud media will supply media service instead of traditional media server in the network. Cloud media is mainly used to process voice/video/data stream in the communication. Based on the requirements of video conference system and the study of the structure of cloud media used in the video conference filed, the key technology points in the application were discussed.